Chemical Vapor Deposition of 2D Vanadium Disulfide and Diselenide and Raman Characterization of the Phase Transitions. Issue 16 (22nd May 2018) - Hossain, Mongur; Wu, Juanxia; Wen, Wen; Liu, Haining; Wang, Xinsheng; Xie, Liming
Abstract: 2D metallic vanadium dichalcogenides (VX2 ) have renewed interest due to their unique physical properties and potential applications as high‐performance functional nanomaterials. Herein, the synthesis and phase transitions of 2D metallic VX2 are investigated. The synthesis is done by chemical vapor deposition using hexagonal boron nitride and mica as substrates. High‐quality VX2 flakes with sub‐10 nm thickness are obtained and characterized by transmission electron microscopy. Temperature‐dependent Raman characterization between 330 and 5 K is conducted and remarkable changes of Raman modes at around 150 K for VS2 flakes and 110 K for VSe2 flakes are revealed, indicating charge density wave phase transitions. Temperature‐dependent electrical measurements have also supported the phase transitions observed in Raman characterization. Abstract : Two‐dimensional metallic vanadium dichalcogenides are synthesized on hexagonal boron nitride and mica by chemical vapor deposition. The phase transitions in the as‐synthesized VS2 and VSe2 flakes are investigated by temperature‐dependent Raman spectroscopy and electrical measurement. The temperature dependent Raman shift, linewidth and intensity are observed at around 150 and 110 K for VS2 and VSe2, respectively.